A STUDY OF THE IMPACT OF THE WAR IN UKRAINE ON PSYCHOSOMATIC HEALTH OF PRESCHOOL CHILDREN IN LITHUANIA: PARENTS’ PERSPECTIVE - Lesinskiene, Sigita; Lapinskaite, Auguste; Kostiuk, Olena; Sambaras, Rokas (International Journal of Child, Youth and Family Studies, 2024)
Lithuanian society supports Ukraine in its war with Russia. The two countries, Lithuania and Russia (the aggressor in the conflict) share a common border in the southwest of Lithuania, and Lithuanians are aware of the threat of an extended war. However, there is little information about how to discuss the events of the ongoing war with children. The aim of our study, which was conducted during the first months of the war, was to investigate the ways that parents talked about the war with their kindergarten-age children, together with their views on the impact of the war on their children’s emotions, behavior, and psychosomatic health. Parents in 5 kindergartens filled out an anonymous 15-item questionnaire, developed by the authors, through which we collected general data about each respondent and their child, their ways of communicating with the child about war events, and the impact of the war events on the parent and on the child’s emotions, moods, and behavior. Of the 116 parents who filled in the questionnaire, 93 (80.2%) responded that they had not talked about war with their children prior to Russia’s invasion, 44.0% of parents responded that they do not talk about the war in Ukraine with their child, and 57.8% parents indicated that their child had asked them about the war. In regard to the war’s effects on children, significant changes were reported in their behavior, play, and drawing. It is crucial to study the effects the recent war has had on children and find appropriate ways in which parents and educational institutions can contribute to their support. Preschoolers need to be informed and involved in the community life in age-appropriate ways. Drawing and play could be used to create relevant opportunities to talk in age-appropriate ways with preschool children about the ongoing war, to try to understand their perceptions, fears, and imaginings.